Terminologi Khalifah dan Pergeseran Maknanya di Indonesia - Basyayif, Syamil; Zaini, Hisyam (JILSA (Jurnal Ilmu Linguistik dan Sastra Arab), 2025)
The word caliph is a word that is quite popular among the Islamic community in general and Indonesian society in particular. Along with its development, with the existence of Islamic movements such as HTI, MMI, and FPI which are oriented towards the establishment of an Islamic state and the enforcement of Islamic law, the word caliph has experienced a shift in meaning in Indonesian society. The focus of this research is to reveal the shift in the meaning of the word caliph in Indonesian society in terms of social historical factors. The research data is in the form of books and journals relevant to the research collected through reading and recording techniques, then analyzing it and explaining the conclusions obtained. The result of this research is that the word khalifah, which basically means ‘behind’ or ‘substitute’, has shifted to become ‘the leader of the Islamic state’, ‘the leader who enforces Islamic law’, and ‘the leader who protects the religion of Islam and the leader who calls the people away from evil things’.